The Influence of Psychopathic Personality Traits, Low Self-Control, and Nonshared Environmental Factors on Criminal Involvement - Boccio, Cashen M. (Youth violence and juvenile justice, 2018)
Theoretical and empirical research has linked variation in parental and peer socialization patterns as well as criminogenic traits, particularly psychopathy and low self-control, to criminal involvement. Findings from this body of scholarship, however, have generally been produced without adequately controlling for genetic confounding. The current study addresses this gap in the literature by analyzing data from the National Longitudinal Study of Adolescent to Adult Health using a genetically informative research design. This study employs monozygotic difference scores analyses in order to examine the effects of psychopathic personality traits (PPTs), low self-control, and nonshared environmental factors on involvement with criminal behavior while controlling for genetic factors. The results indicated that of the four outcomes examined, PPTs were only associated with involvement in violent behavior. In addition, the results revealed that delinquent peers was the only nonshared environmental factor associated with any of the outcome measures.